2018
DOI: 10.1038/s41598-018-34390-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-species oral biofilm promotes reconstructed human gingiva epithelial barrier function

Abstract: Since the oral mucosa is continuously exposed to abundant microbes, one of its most important defense features is a highly proliferative, thick, stratified epithelium. The cellular mechanisms responsible for this are still unknown. The aim of this study was to determine whether multi-species oral biofilm contribute to the extensive stratification and primed antimicrobial defense in epithelium. Two in vitro models were used: 3D reconstructed human gingiva (RHG) and oral bacteria representative of multi-species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 50 publications
(62 reference statements)
7
80
0
Order By: Relevance
“…Taken together, these data suggest that oral mucosa epithelium is intrinsically primed to repair through different mechanisms from that observed in skin, but the large number of epithelial cell layers characteristic of many types of oral mucosa subject to extreme mechanical load and pathogen exposure is most probably regulated by extrinsic factors in the microenvironment. Indeed, Shang et al (2018) have recently shown that commensal oral biofilm has a beneficial influence on oral mucosa barrier function by increasing keratinocyte proliferation, stratification and expression of host-defence proteins.…”
Section: Wound Healing After Tooth Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these data suggest that oral mucosa epithelium is intrinsically primed to repair through different mechanisms from that observed in skin, but the large number of epithelial cell layers characteristic of many types of oral mucosa subject to extreme mechanical load and pathogen exposure is most probably regulated by extrinsic factors in the microenvironment. Indeed, Shang et al (2018) have recently shown that commensal oral biofilm has a beneficial influence on oral mucosa barrier function by increasing keratinocyte proliferation, stratification and expression of host-defence proteins.…”
Section: Wound Healing After Tooth Extractionmentioning
confidence: 99%
“…, when comparing oral commensal and pathogenic biofilms, observed that the pathogenic biofilm supresses the innate immune response (inflammatory cytokine release), suggesting that an early immune evasion is taking place in the organotypic gingival mucosa tissue equivalents. Furthermore, Shang et al (2018), using gingival tissue equivalents, showed that a commensal multi-species oral biofilm promotes an organised epithelial stratification and oral barrier function by increasing epithelial cell layers' number, cell proliferation and expression of host anti-microbial protein expression [elafin, human beta defensin (HBD) 2 and HBD3).…”
Section: Biofilmmentioning
confidence: 99%
“…The formation of oral biofilms can provide protected microenvironments for microbial communities at different colonization sites, along with the establishment of an oral microecology. It is undeniable that both a stable ecological environment and the diversity of oral microecology have positive effects on maintaining oral health and oral mucosal barriers, and reach a symbiotic relation with the host. When examining any antibacterial material for the control of oral biofilm‐related diseases, it is important to focus on its possible effects on oral microecology, and to eliminate one‐sided thinking that only focuses on its antibacterial properties.…”
Section: The Possible Influence Of Nanomaterials On Oral Microecologymentioning
confidence: 99%
“…When studying the antioral biofilm properties of nanoparticles, it is not advisable to ignore the possible adverse effects on oral microecology and only examine the ability to kill bacteria. Studies have shown that microbial communities in the oral cavity may have a beneficial effect on oral mucosal barriers . At the same time, the diversity of an oral biofilm microecology has a positive effect on maintaining oral health.…”
Section: The Possible Influence Of Nanomaterials On Oral Microecologymentioning
confidence: 99%
See 1 more Smart Citation